Role and importance of choreography in gymnastic and dance sports - Артем’єва, Галина; Мошенська, Тетяна (Slobozhanskyi Herald of Science and Sport, 2018)
Galyna Artemyeva & Tetiana Moshenska Choreographic component is mandatory for the construction of competitive programs in gymnastic and dance sports, and when presenting an assessment for the performed composition, choreography is one of the criteria, according to one of the types of training in these sports there is choreographic. Purpose: the establishment of the role of choreography in the training of athletes in gymnastic and dance sports, and its importance in the evaluation of competitive activities. Material & Methods: for the conduct of this study, the following methods were used: theoretical – analysis and generalization of literary sources; sociological – questioning. The study was conducted with specialists who develop gymnastic and dance sports. In the questionnaire, experienced trainers in sports aerobics, cheerleading and acrobatic rock and roll took part in the number of 24 respondents (8 from each of the presented sports). An important aspect in the preparation of successful athletes in gymnastic and dance sports is the rational combination of different types of training in the multi-year training process. Results: because of the weak theoretical basis in these sports there is a lack of research on this issue, indisputably practitioners have a question about the degree of influence of the choreography on the final result, and the inclusion in the training process of the necessary amount of its funds. The conducted research has allowed to generalize answers of respondents to questions of the questionnaire on the role and significance of choreography when building a training process with athletes in gymnastic and dance sports. Conclusion: obtained results do not indicate that today choreography is an integral component of both the training process and the competitive activity. But in each of the sports presented there is an ambiguous attitude of practitioners to the choreographic preparation and inclusion of its resources in the training process.